The Brazilian women’s movement and the state under the PT national governments - Bohn, Simone; Levy, Charmain (European Review of Latin American and Caribbean Studies, 2019)
Certain segments of the Brazilian Women’s Movement (BWM) developed important strategic partnerships with the state under the PT federal government. This article demonstrates how these partnerships had both inclusionary and exclusionary effects on gender-centric policy outcomes. Using a mix-method approach which includes extensive in-depth interviews with BMW activists and archival data from governmental sources, the Brazilian experience illustrates that “entering the state” headed by a women-ally president facilitates funnelling some of the women’s movement’s demands into the state. However, hierarchies within the movement itself, the congressional strength of the head of executive and the activism of some of its socially-conservative legislative allies can severely temper that effect. Resumen: El movimiento de mujeres brasileñas y el Estado durante los gobiernos nacionales de PTCiertos segmentos del Movimiento de Mujeres Brasileñas (BWM) desarrollaron importantes alianzas estratégicas con el estado bajo el gobierno federal del PT. Este artículo demuestra cómo estas asociaciones tuvieron efectos tanto inclusivos como excluyentes en los resultados de las políticas de género. Utilizando un método mixto que incluye extensas entrevistas en profundidad con activistas de BMW y archivos de fuentes gubernamentales, la experiencia brasileña ilustra que “entrar en el Estado” encabezado por un presidente aliado de las mujeres facilita canalizar algunas de las demandas del movimiento de mujeres hacia el Estado. Sin embargo, las jerarquías dentro del movimiento, la fuerza congresional del jefe ejecutivo y el activismo de algunos de sus aliados legislativos socialmente conservadores pueden moderar severamente ese efecto.